Immune checkpoint inhibitor-induced colitis with endoscopic evaluation in Chinese cancer patients: a single-centre retrospective study - Furong Kou; Furong Kou; Jian Li; Yanshuo Cao; Zhi Peng; Ting Xu; Lin Shen; Jifang Gong; Xicheng Wang (Frontiers in Oncology, 2023)
BackgroundWe investigated the clinical and endoscopic features, management strategies, and outcomes of Chinese cancer patients with immune checkpoint inhibitor (ICI)-induced colitis.MethodThis single-centre retrospective study included patients who developed ICI-induced colitis and underwent endoscopic evaluation from June 1, 2019 to October 1, 2023. We analysed clinical features, ICI-induced colitis-related information, management strategies, and outcomes.ResultsA total of 25 patients were included; most were male (88%) with a median age of 59 years. Eleven (44%) patients had grade 2 colitis, and 14 (56%) had grade 3 colitis. The median time from ICI initiation to colitis onset was 105 days. The median duration from symptom onset to endoscopic evaluation was 11 days. Regarding endoscopic evaluation, colitis involved the entire colon in 13 (52%) patients, and 15 (60%) had ulcers. Twenty-three (92%) patients received steroids, and 3 (12%) added infliximab (IFX). Most patients (n=19, 76%) achieved remission with complete tapering of the steroid taken for the first colitis episode. Among the 6 (24%) patients who did not taper initial, 5 patients increased their steroid dosage with 2 added IFX, leading to symptom remission and successful steroid tapering, while one patient experienced continuous non-remission despite increasing the steroid and receiving two infusions of IFX. Of the 8 (32%) ICI rechallenge patients, 4 achieved long-lasting benefit without colitis recurrence. The other 4 experienced recurrent colitis after ICI rechallenge and permanently discontinued ICIs. The median duration from ICI rechallenge to colitis recurrence was shorter than the time to colitis onset. One patient developed steroid-refractory colitis and recovered with one infusion of IFX.ConclusionEndoscopy has value in the evaluation and optimal management of ICI-induced colitis in Chinese cancer patients. IFX is necessary for treating colitis, especially in steroid-refractory/resistant patients. ICI rechallenge can achieve benefit, but permanently discontinuing ICIs is needed if colitis recurs. Future large-scale prospective studies are required for more accurate assessments and validation.